2022
DOI: 10.3390/ijms232213959
|View full text |Cite
|
Sign up to set email alerts
|

C Type Natriuretic Peptide Receptor Activation Inhibits Sodium Channel Activity in Human Aortic Endothelial Cells by Activating the Diacylglycerol-Protein Kinase C Pathway

Abstract: The C-type natriuretic peptide receptor (NPRC) is expressed in many cell types and binds all natriuretic peptides with high affinity. Ligand binding results in the activation or inhibition of various intracellular signaling pathways. Although NPRC ligand binding has been shown to regulate various ion channels, the regulation of endothelial sodium channel (EnNaC) activity by NPRC activation has not been studied. The objective of this study was to investigate mechanisms of EnNaC regulation associated with NPRC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…EnNaC) with a conductance of 16pS. In a previous study we reported the expression of a 25pS channel in human aortic endothelial cells (7). As expected, single channel characteristics of various ion channels could be different among species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…EnNaC) with a conductance of 16pS. In a previous study we reported the expression of a 25pS channel in human aortic endothelial cells (7). As expected, single channel characteristics of various ion channels could be different among species.…”
Section: Discussionmentioning
confidence: 99%
“…Our group previously showed the function of EnNaC is negatively regulated by activation of the NPRC and inhibition of NPRC results in an increase in EnNaC activity (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 NPR-C, which is encoded by the Npr3 gene, has no guanylate cyclase domain 28 and was originally thought to function primarily as a clearance receptor, although it has also been shown to have potential signaling mechanisms via activation of Gcoupled proteins or phosphatidylinositol-4,5-biphosphate (PIP 2 ). 29,30 The receptors that mediate the protective effect of ANP on ALI are not known, however, studies by our lab suggest that both NPR-A and NPR-C may play a role. Previously, we have shown that ANP attenuates LPS-induced pulmonary edema even in the absence of NPR-A.…”
Section: Introductionmentioning
confidence: 89%
“…Ligand binding results in activation of the guanylyl cyclase and synthesis of cGMP, which is thought to mediate most of the biological properties of the natriuretic peptides 27 . NPR‐C, which is encoded by the Npr3 gene, has no guanylate cyclase domain 28 and was originally thought to function primarily as a clearance receptor, although it has also been shown to have potential signaling mechanisms via activation of G‐coupled proteins or phosphatidylinositol‐4,5‐biphosphate (PIP 2 ) 29,30 . The receptors that mediate the protective effect of ANP on ALI are not known, however, studies by our lab suggest that both NPR‐A and NPR‐C may play a role.…”
Section: Introductionmentioning
confidence: 99%